Towards Property Profiling: SYNTHESIS and SAR Probing of New Tetracyclic Diazaphenothiazine Analogues - Empel, Anna; Bak, Andrzej; Kozik, Violetta; Latocha, Malgorzata; Cizek, Alois; Jampilek, Josef; Suwinska, Kinga; Sochanik, Aleksander; Zieba, Andrzej (International journal of molecular sciences, 2021)
A series of new tertiary phenothiazine derivatives containing a quinoline and a pyridine fragment was synthesized by the reaction of 1-methyl-3-benzoylthio-4-butylthioquinolinium chloride with 3-aminopyridine derivatives bearing various substituents on the pyridine ring. The direction and mechanism of the cyclization reaction of intermediates with the structure of 1-methyl-4-(3-pyridyl)aminoquinolinium-3-thiolate was related to the substituents in the 2- and 4-pyridine position. The structures of the compounds were analyzed using 1H, 13C NMR (COSY, HSQC, HMBC) and X-ray analysis, respectively. Moreover, the antiproliferative activity against tumor cells (A549, T47D, SNB-19) and a normal cell line (NHDF) was tested. The antibacterial screening of all the compounds was conducted against the reference and quality control strain Staphylococcus aureus ATCC 29213, three clinical isolates of methicillin-resistant S. aureus (MRSA). In silico computation of the intermolecular similarity was performed using principal component analysis (PCA) and hierarchical clustering analysis (HCA) on the pool of structure/property-related descriptors calculated for the novel tetracyclic diazaphenothiazine derivatives. The distance-oriented property evaluation was correlated with the experimental anticancer activities and empirical lipophilicity as well. The quantitative shape-based comparison was conducted using the CoMSA method in order to indicate the potentially valid steric, electronic and lipophilic properties. Finally, the numerical sampling of similarity-related activity landscape (SALI) provided a subtle picture of the SAR trends.
Keywords: Anti-Bacterial Agents; azaphenothiazines; phenothiazine; similarity-activity landscape index; pharmacophore mapping; lipophilicity; fenothiaziny; Tumor Cells, Cultured; Microbial Sensitivity Tests; Antineoplastic Agents; Staphylococcus aureus; antibacterial activity; heterocyklické sloučeniny; Neoplasms; Heterocyclic Compounds; protinádorové látky; vztahy mezi strukturou a aktivitou; Humans; nádory; antibakteriální látky; antiproliferative activity; mikrobiální testy citlivosti; Structure-Activity Relationship; nádorové buňky kultivované; lidé; Phenothiazines